Optimizing Power Consumption for Sustainable Dry Turning of Treated Aluminum Alloy - Nur, R.; Kurniawan, Denni; Noordin, M.; Izman, S. (2015)
© 2015 The Authors Machining companies can implement sustainable manufacturing using steps to improving the performance of economic, environmental and social. One of the steps is to perform the efficiency of energy consumption (mainly electricity) in machining. This paper describes a case study which investigates the effect of cutting parameters on power consumption and surface roughness by applying design of experiments. Dry turning of treated Al-11%Si alloy using coated carbide tool at different cutting speed (70, 130 and 250 m/min) and feed (0.05, 0.10 and 0.15 mm) was investigated. The results showed an optimum effect of cutting parameters that was obtained at low feed rate and high cutting speed, as shown by the model solutions.